2021
DOI: 10.1016/j.jinf.2020.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Medical features of COVID-19 and influenza infection: A comparative study in Paris, France

Abstract: Highlights COVID-19 and influenza patients share overweight as a risk factor for severe infection. Higher death rate was reported in COVID-19 group than in influenza group. COVID-19 patients developed preferentially secondary respiratory failure. Older age and diabetes were confirmed as major contributing death risk factors in COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 7 publications
6
42
0
Order By: Relevance
“…Not only was the risk of complication higher, they also had a longer hospital LOS and considerably higher in-hospital mortality. These ndings have been reported by others and support the current notion of COVID-19 being a more hazardous condition than seasonal in uenza, at least for hospitalized patients [14,25].…”
Section: Discussionsupporting
confidence: 91%
“…Not only was the risk of complication higher, they also had a longer hospital LOS and considerably higher in-hospital mortality. These ndings have been reported by others and support the current notion of COVID-19 being a more hazardous condition than seasonal in uenza, at least for hospitalized patients [14,25].…”
Section: Discussionsupporting
confidence: 91%
“…Fever and respiratory symptoms such as cough, expectoration or sputum production and dyspnea were the main symptoms in both groups with COVID-19 and influenza; however, they were significantly more frequent in patients with influenza [ 5 , 9 , 10 , 11 , 13 , 15 , 16 , 19 , 20 ]. Moreover, vomiting, otorhinolaryngological symptoms such as nasal congestion, rhinorrhea, sore throat and ocular symptoms such as tearing and conjunctival hyperhemia were statistically more frequent in patients with influenza than COVID-19 adult patients [ 5 , 10 , 11 , 12 , 15 ]. In patients infected with COVID-19, the most significant and frequent clinical features were fatigue, neurologic symptoms such as headache (especially facial headache: retro-orbital or frontal headache), anosmia and dysgeusia, gastro-intestinal (GI) symptoms such as diarrhea and acute respiratory distress syndrome (ARDS), compared to influenza patients [ 11 , 13 , 14 , 15 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this review, 14 studies of 18 [ 5 , 6 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 18 , 19 , 20 , 21 ] reported a comparison between COVID-19 and influenza patients based on demographic findings, comorbidities, clinical features, and outcome ( Table 2 ). Fever and respiratory symptoms such as cough, expectoration or sputum production and dyspnea were the main symptoms in both groups with COVID-19 and influenza; however, they were significantly more frequent in patients with influenza [ 5 , 9 , 10 , 11 , 13 , 15 , 16 , 19 , 20 ]. Moreover, vomiting, otorhinolaryngological symptoms such as nasal congestion, rhinorrhea, sore throat and ocular symptoms such as tearing and conjunctival hyperhemia were statistically more frequent in patients with influenza than COVID-19 adult patients [ 5 , 10 , 11 , 12 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] In the UK, as the second wave is coinciding with the winter months, clinicians are faced with further complexity in the diagnosis of COVID-19 due to the similar symptomology with other viral respiratory illnesses. [5,6] Ensuring a detailed understanding of identi cation and management strategies adopted during the rst wave of infections is crucial in order to inform the design of effective clinical pathways for admitted patients. There is pressure to expedite test development and evaluation, and the demand on developing models to help identify optimal testing strategies is also high.…”
Section: Introductionmentioning
confidence: 99%